The Catena in Marcum a Byzantine anthology of early commentary on Mark - Lamb, William R. S. (Leiden : BRILL, 2012)
Providing the first extended English translation of the earliest anthology of patristic commentary on Mark's gospel, this book provides a careful analysis of the development of this text and assesses its significance for the history of the interpretation of Mark's gospel.
27. On the quarrels about who is the greatestChapter 10; 28. On the Pharisees who asked questions; 29. On the rich man who questioned Jesus; 30. On the sons of Zebedee; 31. On Bartimaeus; Chapter 11; 32. On the colt; 33. On the withered fig tree; 34. On the capacity for forgiveness; 35. On the chief priests and scribes who questioned the Lord; Chapter 12; 36. On the vineyard; 37. On those sent to ask about the poll tax; 38. On the Sadducees; 39. On the scribe; 40. On questioning from the Lord; 41. On the two coins; Chapter 13; 42. On the end; 43. On that day and that hour; Chapter 14.
44. On the woman who anointed the Lord with sweet perfume.
Description based on print version record.
Keywords: Bible; Bible. N.T. Mark -- Commentaries -- Early works to 1800.; Bible. N.T. Mark -- Criticism, interpretation, etc; Bible. N.T. Mark; Religion; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Bible. -- Commentaries -- Early works to 1800.; Bible. -- Criticism, interpretation, etc; Electronic books